2008
DOI: 10.1103/physrevlett.101.055502
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Electrical Conductivity inSnO2

Abstract: SnO 2 is widely used as a transparent conductor and sensor material. Better understanding and control of its conductivity would enhance its performance in existing applications and enable new ones, such as in light emitters. Using density functional theory, we show that the conventional attribution of n-type conductivity to intrinsic point defects is incorrect. Unintentional incorporation of hydrogen provides a consistent explanation of experimental observations. Most importantly, we find that SnO 2 offers exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
253
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(273 citation statements)
references
References 32 publications
17
253
1
2
Order By: Relevance
“…Kılıç and Zunger [56] found that Sn-interstitials were shallow donors in SnO 2 , and furthermore had a low formation energy, causing them to attribute such defects as the probable source of conductivity in this material. Subsequent theoretical studies [57,68], however, suggested that the formation energy for isolated Sn-intersitials is actually very high for n-type material, indicating that such defect centres would be unlikely to be present in significant quantities in SnO 2 . Furthermore, their calculated migration barrier is very low [57], leading to doubts over the stability of such centres.…”
Section: Cation Interstitialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kılıç and Zunger [56] found that Sn-interstitials were shallow donors in SnO 2 , and furthermore had a low formation energy, causing them to attribute such defects as the probable source of conductivity in this material. Subsequent theoretical studies [57,68], however, suggested that the formation energy for isolated Sn-intersitials is actually very high for n-type material, indicating that such defect centres would be unlikely to be present in significant quantities in SnO 2 . Furthermore, their calculated migration barrier is very low [57], leading to doubts over the stability of such centres.…”
Section: Cation Interstitialsmentioning
confidence: 99%
“…Subsequent theoretical studies [57,68], however, suggested that the formation energy for isolated Sn-intersitials is actually very high for n-type material, indicating that such defect centres would be unlikely to be present in significant quantities in SnO 2 . Furthermore, their calculated migration barrier is very low [57], leading to doubts over the stability of such centres. Interstitial zinc has also been attributed as the cause of n-type conductivity in ZnO [69].…”
Section: Cation Interstitialsmentioning
confidence: 99%
“…In this way, it is possible to have a simultaneous high carrier concentration with minor effects on transparency [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact tin oxide is a transparent conductive oxide even in its undoped state. The conductivity is due to an intrinsic non-stoichiometry, created by the presence of oxygen vacancies (V o ) and interstitial tin (Sn i ) inside the structure, which are easily tolerated due to the multivalence of tin [3,4]. Spontaneous acceptor-like intrinsic defects, like interstitial oxygen or tin vacancies are absent, therefore the electrons released by the V o or Sn i are not compensated.…”
Section: Introductionmentioning
confidence: 99%
“…Among those, SnO 2 exhibits a direct band gap of 3.6 eV, high exciton binding energy (130 meV) and high carrier mobility (around 250 cm 2 /Vs) [5], which makes it a promising host material for next-generation optoelectronic devices and extensively used for transparent electrodes [6]. Even solution synthesized transparent p-type conducting thin films have been previously reported by doping SnO 2 with In or In-Ga [7][8][9].…”
Section: Introductionmentioning
confidence: 99%